WAYS TO MANAGE HEATING INERTIA - Biloshytskyi, E. V. (Science and Transport Progress, 2017)
Purpose. The research paper proposes to estimate the effect of heat inertia of the water heating system, in transient operation modes, on the temperature condition in the passenger car, as well as to offer technical solutions intended to reduce the heating system inertia effect and to maintain a stable temperature condition in the passenger car premises in transitional modes of the heating system. Methodology. The author developed the method for controlling the heat transfer of heating system pipes with the help of regulating casing. To control the heating system and the heat transfer of heating pipes, two types of temperature control sensors were used in the passenger car: certain sensors interacted with regulatory casings, while the others interacted with high-voltage tubular heating element control devices. To assess the efficiency of heat interchange regulation of heating pipes and the heating system control, with installed regulating casings, the operation of the heating system with regulating casings and two types of sensors was mathematically modelled. Mathematical modelling used the experimental test data. The results of experimental tests and mathematical modelling were compared. Findings. Currently in operated passenger cars, control of heating appliances is not constructively provided. Automatic maintenance of the set temperature in a passenger car is limited to switching on and off of high-voltage tubular heating elements. The use of regulating casings on heating pipes allows reducing the effects of heat inertia and maintaining stable thermal conditions in a passenger car, using the heating system as a heat accumulator, and also provides the opportunity to realize an individual control of air temperature in the compartment. Originality. For the first time, the paper studied the alternative ways of regulating the temperature condition in a passenger car. Using of the heating system as a heat accumulator. Practical value. The regulation of the heat transfers of the heating pipes by regulating casings allows reducing the effect of thermal inertia of the heating system on the temperature condition in a passenger car, implementing individual adjustment of air temperature in a compartment within 40% of the power of the heating pipe section, using the heating system as a heat accumulator.